Resposta :
Resposta:
5
Explicação passo-a-passo:
7 - (-3) + (+1) - 6 =
7 + 3 + 1 - 6 =
11 - 6 =
5
Resposta:
5
Explicação passo-a-passo:
primeiro eu calculei, depois fui na calculadora pra ver se estava correto, e estava, espero ter te ajudado :)
![Ver imagem MARYERDRGS](https://pt-static.z-dn.net/files/d7e/4b777cdc7364ce9d0ef64893d64148e2.jpg)
Resposta:
5
Explicação passo-a-passo:
7 - (-3) + (+1) - 6 =
7 + 3 + 1 - 6 =
11 - 6 =
5
Resposta:
5
Explicação passo-a-passo:
primeiro eu calculei, depois fui na calculadora pra ver se estava correto, e estava, espero ter te ajudado :)